In Defense of the Author* - Madoyan, Gohar (Armenian Folia Anglistika, 2013)
The concept of the author has been surrounded by much controversy since the early years of literature. It was heavily discussed in the antique period and was “crowned” in the era of Romanticism. However, in the 20th century and along with the advancement of the ideas of an individuality, human rights and equality, new philosophical directions sprang which cast doubt at the previously held traditional views and approaches. Structuralists and later post-structuralists “killed” the author enhancing the role of the reader. But has the author died? Maybe he is just dozing?* The title makes reference to an essay by E.R. Hirsch.